O Movimento #MeToo: Argumentação, enviesamento e negação polémica - Magalhães, Violeta (Language and Law / Linguagem e Direito, 2022)
In this article we present a forensic analysis of the most relevant argumentative mechanisms in opinion pieces produced about the #MeToo Movement. A corpus of 28 opinion pieces published in the newspapers Expresso, Observador and Público between October 2017 and February 2020 was created to analyze the linguistic mechanisms that most contributed to the defense of a certain point of view (in favor or against the movement). A lexical analysis showed the bias of the discourses, while an analysis of negation showed the presence and exploitation of the multiple voices that coexist in a discourse. It is our goal to affirm discourse as a place of power, as well as to reiterate the role of language as powerful forensic evidence of mental and social schemata that precede argumentation.